Access to Care Among Individuals Who Experienced Medicaid Lockouts After Premium Nonpayment - Saloner, Brendan (JAMA Netw Open, 2019)
This survey study compares the demographic characteristics, access to care, and health status of recent Medicaid enrollees in Wisconsin with and without experience of Medicaid lockouts.